Enhanced anaerobic degradation of quinoline and indole with the coupling of sodium citrate and polyurethane. Issue 26 (23rd November 2021) - Shi, Jingxin; Huang, Wenping; Xu, Chunyan; Han, Yuxing; Han, Hongjun
ABSTRACT: A coupling system of sodium citrate and biofilm based on polyurethane was prepared to analyse the coupling enhancement degradation on quinoline and indole. Four reactors (R1: sludge, R2: sludge + sodium citrate, R3: biofilm on polyurethane, and R4: biofilm + sodium citrate) were operated 120 days to compare the degradation efficiency. During whole running phases, R4 showed high degradation efficiency on quinoline (≥98.55%) and indole (≥95.44%). Analysis of bacterial colony showed anaerobic sludge reactors benefited the enrichment of Aminicenantes, Levilinea, and Longilinea, while anaerobic biofilm reactors benefited the enrichment of Giesbergeria and Comamonas . Furthermore, analysis of archaea colony showed acetic acid metabolism to produce methane was the main mode in anaerobic sludge reactors, while acetic acid and hydrogen metabolism to produce methane were both the main modes in biofilm reactors. This study can provide some references for the treatment of nitrogen heterocyclic wastewater. GRAPHICAL ABSTRACT: UF0001